Profile of Estrogen Metabolism in Endometriosis Patients - Verani, Tirsa; Sumapradja, Kanadi (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To assess the estrone (E1), estradiol (E2) and estriol (E3) blood level and its ratio (E2:E1, E2:E3 and E1:E3) between women with and without endometriosis. Method: We performed an analytical cross sectional study with 27 women with endometriosis and 27 women without endometriosis who met the inclusion criteria. The samples were recruited in Dr. Cipto Mangunkusumo hospital and other satellite hospitals from October 2012 to April 2013. The blood level of estrogen metabolites was examined by enzyme-linked immunosorbent assay (ELISA). Comparison between the two groups was analyzed by using Mann- Whitney test. Result: The level of estrone was found to be lower in endometriosis group compared to that in the control group (54.66 pg/ml vs 73.52 pg/ml, p=0.229). Similarly, the levels of estradiol and estriol were lower in endometriosis group (29 pg/ml vs 35 pg/ml, p=0.815 and 1.11 pg/ml vs 1.67 pg/ml, p=0.095, consecutively). The E2:E1 ratio was higher in endometriosis group (0.51 pg/ml vs 0.38 pg/ml, p=0.164), as well as E2:E3 ratio (26.53 pg/ml vs 21.11 pg/ml, p=0.223) and the E1:E3 ratio (58.55 pg/ml vs 50.28 pg/ml, p=0.684). However, all those differences were not statistically significant. Conclusion: The estrone, estradiol and estriol levels in women with endometriosis were lower compared to those in women without endometriosis. The ratio of E2:E1, E2:E3 and E1:E3 were higher in endometriosis group. However, all those differences failed to reach statistical significance. [Indones J Obstet Gynecol 2014; 3: 127-131] Keywords: endometriosis, estradiol, estriol, estrogen, estrone